(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
As a result of the first multiparty elections on October 28, 1990, instead of the communist regime, the national government came to power in the Republic of Georgia in the form of a bloc "Round Table - Free Georgia", Led by well-known dissident Zviad Gamsakhurdia, leader of the National Liberation Movement. The new government inherited a bad legacy. Conflict zones were artificially created in different parts of Georgia. Particularly cautious approaches were needed to the regions with autonomous status. These were: the Autonomous Soviet Socialist Republic of Adjara (ASSR), the Autonomous Soviet Socialist Republic of Abkhazia (ASSR) and so-called South Ossetia Autonomous District.